2022
DOI: 10.1111/jam.15477
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and virulence genes inSalmonella entericaserovars isolated from droppings of layer chicken in two farms in Nigeria

Abstract: Aim This study aimed to investigate the isolation rate, antibiotic resistance and virulence genes of Salmonella enterica serovar from two commercial farms in Nigeria. Methods and Results Salmonella isolation was performed according to the United States Food and Drug Agency (USFDA) method. Serotyping, antimicrobial susceptibility testing, detection of resistance and virulence genes were done using the Kauffman–White Scheme, disc diffusion, minimum inhibitory concentration and real‐time polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 95 publications
1
6
1
Order By: Relevance
“…In their study, the most S. Enteritidis isolates (84.0%, n = 21/25) harbored tetA gene, whereas the tetB gene was only found in 2 isolates [ 18 ]. However, in another report by Shittu et al [ 27 ] from Nigeria, the tetA and tetB genes were not detected in any S. enterica serovars including S. Enteritidis isolates that was in contrast to our results. In another research by Siddiky et al [ 26 ] from Bangladesh, tetA and sul1 genes were detected in 3.44% of S. Enteritidis isolates that was lower than our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In their study, the most S. Enteritidis isolates (84.0%, n = 21/25) harbored tetA gene, whereas the tetB gene was only found in 2 isolates [ 18 ]. However, in another report by Shittu et al [ 27 ] from Nigeria, the tetA and tetB genes were not detected in any S. enterica serovars including S. Enteritidis isolates that was in contrast to our results. In another research by Siddiky et al [ 26 ] from Bangladesh, tetA and sul1 genes were detected in 3.44% of S. Enteritidis isolates that was lower than our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, Wang et al [31] from China reported higher incidence rates for sopB (100.0%) and spvC (93.8%) genes among Salmonella serovars isolated from 120 retail meat samples, including chicken (n = 45), duck (n = 30), and pork (n = 45). In the prior studies from Iran [6], Tunisia [23], and Nigeria [27], the prevalence rates of spvC gene were 50.8%, 45.8%, and 59.1%, respectively. In line with our results, Khodadadipour et al [32] from Iran detected the phoP/Q gene (33.3%) as the most prevalent virulence determinant in S. Enteritidis strains isolated from meat and egg samples.…”
Section: Discussionmentioning
confidence: 99%
“…These are essential for Salmonella to survive in the host environment and enter non-phagocytic cells. Animal waste commonly allows Salmonella to enter agricultural environments [76]. Plants and surface water used for irrigation or as a diluent for pesticides or fertilizers may be directly contaminated by animal feces [77].…”
Section: Transmission Of Antibiotic-resistant S Enterica In Humans An...mentioning
confidence: 99%
“…Suppose the antibiotic resistances seen in human bacterial isolates are closely related to those seen in animal Salmonella enterica Transmission and Antimicrobial Resistance Dynamics across One-Health… DOI: http://dx.doi.org/10.5772/intechopen.109229 isolates. In that case, it may be possible to identify animal sources of resistant bacteria in human infections that can be targeted to reduce human disease [76,90,91]. This can be done by determining if the resistances seen in human bacterial isolates are similar to those seen in animal isolates [92].…”
Section: Antimicrobial Resistance Of S Enterica From Humans Animals A...mentioning
confidence: 99%
See 1 more Smart Citation